2020
DOI: 10.21037/atm-20-3749
|View full text |Cite
|
Sign up to set email alerts
|

miR-328-3p overexpression attenuates the malignant proliferation and invasion of liver cancer via targeting Endoplasmic Reticulum Metallo Protease 1 to inhibit AKT phosphorylation

Abstract: Background: Liver cancer is one of the most common cancers worldwide. microRNAs (miRNAs) have been recognized as minimally invasive prognostic markers for distinct types of cancer. This study evaluates the mitigation role of miR-328-3p on liver cancer in vitro and in vivo.Methods: Liver cancer cell line Huh-7 and HepG2 were used for in vitro experiments. Compared with the control group, miR-328-3p overexpression inhibited the proliferation, invasion, and promoted apoptosis of Huh-7 cells. miR-328-3p and endopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Zhang et al also showed downregulation of miR-328-3p in penile cancer tissues relative to adjacent non-cancerous tissues by Next-Generation Small RNA Sequencing [ 42 ]. MiRmiR-328-3p inhibits metastasis in colorectal cancer via inactivation of the PI3K/Akt signaling pathway [ 58 ] and reduces invasion as well as EMT in liver cancer via by targeting endoplasmatic reticulum metallo protease 1 ( ERMP1 ) to inhibit AKT phosphorylation [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al also showed downregulation of miR-328-3p in penile cancer tissues relative to adjacent non-cancerous tissues by Next-Generation Small RNA Sequencing [ 42 ]. MiRmiR-328-3p inhibits metastasis in colorectal cancer via inactivation of the PI3K/Akt signaling pathway [ 58 ] and reduces invasion as well as EMT in liver cancer via by targeting endoplasmatic reticulum metallo protease 1 ( ERMP1 ) to inhibit AKT phosphorylation [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found Nrf2 could activate the AKT/p21 pathway, resulting in increased cell cycle progression of HCC cells 23 . Lu et al reported that miR‐328‐3p overexpression inhibited the PI3K/AKT pathway to attenuate the malignant proliferation and invasion of liver cancer 39 . A mechanism explaining the link between induction of AKT activation and concomitant repression of ERα activation is reported in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ER-related miRNAs play a crucial role in cancer proliferation, metastasis and apoptosis. For example, the overexpression of miR-328-3p, targeting ER metalloprotease 1 (ERMP1), prevented liver cancer cell proliferation and invasion in female nude mice by reducing phosphorylation [92]. RT-qPCR analyses of biopsy specimens and cell lines verified that miR-370 is upregulated in gastric cancer, and Circ_002117 inhibits miR-370 to stimulate ER stress-induced apoptosis [93].…”
Section: Endoplasmic Reticulummentioning
confidence: 99%